Healthcare workers’ perceptions and attitudes towards the UK’s COVID-19 vaccination programme: a rapid qualitative appraisal - Manby, L; Dowrick, A; Karia, A; Maio, L; Buck, C; Singleton, G; Lewis-Jackson, S; Uddin, I; Vanderslott, S; Martin, S; Vindrola-Padros, C (BMJ Publishing Group, 2022)
Objectives While there is research relating to perceptions of vaccines among healthcare workers (HCWs), the evidence base in relation to COVID-19 remains limited. The aim of this study was to explore HCWs’ perceptions and attitudes towards vaccines and the COVID-19 vaccination programme in the UK, including their expectations and views on promoting vaccination to others.